2013
DOI: 10.1007/s12185-013-1460-3
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of cyclophosphamide in the modified BuCy regimen with fludarabine is associated with increased incidence of severe pneumonia: a prospective, randomized study

Abstract: The modified busulfan-cyclophosphamide (mBuCy) regimen, combined with hydroxyurea, cytarabine and semustine, is the most frequently used myeloablative conditioning regimen for allogeneic hematopoietic stem cell transplantation in our unit. It is unknown, however, whether fludarabine can be substituted for cyclophosphamide in the mBuCy regimen. We carried out a prospective study to compare modified busulfan-fludarabine (mBuF) with mBuCy, aiming to reduce the treatment-related mortality, with non-inferiority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Our search yielded 197 potentially relevant trials of which 11 [7][8][9][10][11][12][13][14][15][16][17] were considered for further investigation. Of these, five studies were excluded [13][14][15][16][17] ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search yielded 197 potentially relevant trials of which 11 [7][8][9][10][11][12][13][14][15][16][17] were considered for further investigation. Of these, five studies were excluded [13][14][15][16][17] ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Potentially relevant trials identified and screened for retrieval (n=197) Full text articles retrieved for more detailed evaluation (n=11) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) Non-comparative trials (n=188)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations